2014
DOI: 10.1103/physrevlett.112.143902
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Effects in Noncollinear High-Order Harmonic Generation

Abstract: We study two-color high-order harmonic generation using an intense driving field and its weak second harmonic, crossed under a small angle in the focus. Employing sum-and difference-frequency generation processes, such a noncollinear scheme can be used to measure and control macroscopic phase matching effects by utilizing a geometrical phase mismatch component, which depends on the noncollinear angle. We further show how spatial phase effects in the generation volume are mapped out into the far field allowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 27 publications
0
53
0
Order By: Relevance
“…Previous investigations of noncollinear HHG have shown that phase matching effects can determine the angle of preferential harmonic emission and used this angular dependence to infer the difference in the magnitude of the harmonic and driving laser wavevectors [43]. In this work, we experimentally and theoretically investigate the macroscopic physics of phasematched noncollinear HHG at high pressures.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous investigations of noncollinear HHG have shown that phase matching effects can determine the angle of preferential harmonic emission and used this angular dependence to infer the difference in the magnitude of the harmonic and driving laser wavevectors [43]. In this work, we experimentally and theoretically investigate the macroscopic physics of phasematched noncollinear HHG at high pressures.…”
Section: Introductionmentioning
confidence: 98%
“…Due to the angular separation between the driving laser beams, phase-matching in noncollinear HHG [41,43] is fundamentally different from either single-beam HHG or collinear HHG [3,24,[44][45][46][47] and presents both new challenges and new opportunities. Previous investigations of noncollinear HHG have shown that phase matching effects can determine the angle of preferential harmonic emission and used this angular dependence to infer the difference in the magnitude of the harmonic and driving laser wavevectors [43].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations